Badil - Vera, Rody; Hilario, Jhong; Gil, Nikki; Israel, Dick; Roño, Chito C.; Sineng Pambansa (Firm). ([Place of production not identified] Sineng Pamabansa, 2013)
"Acting as a window into how flawed our basic political right has become, the film follows Nonoy as he takes over his Father, the Kapitan's, duties as guardian to committed voters harassed by vote buyers on the eve of the election."
"Summary taken from https://www.imdb.com/title/tt3184764
Produced by Hanz Salazar; music by Carmina Cuya; cinematography by Neil Daza.
Jhong Hilario, Nikki Gil, Dick Israel.
DVD
In Tagalog
Keywords: Drama